Administrative Offence - Criminal Misdemeanor - Crime. Perspectives and Criteria Three-Tier Delictolisation in Russia - Sergei M. Zyryanov (Сибирское юридическое обозрение, 2017)
This article discusses issues of the classification and systematization of public-legal delicts in legislation on administrative offences and the criminal legislation of the Russian Federation. It is noted that the legislation on administrative offences and criminal legislation evolve in different directions; a negative assessment of current trends of development of the legislation on administrative offences is given; attention is drawn to dangerous social consequences of such a development.The Author assesses the proposal on the formation of an independent category of delicts “criminal misdemeanor” and draws attention to the fact that in the Russian legislation already has a multilevel delictolisation and the inclusion of several intermediate levels of criminal offences does not affect the situation.According to the Author, administrative offences and crimes have a common legal nature, as evidenced by the numerous attempts by Russian and Soviet scientists to distinguish between them by any criteria, and should be in a single system that would ensure the proportionality of the coercive State importance protected by legislation values.